2007
DOI: 10.1158/1078-0432.ccr-06-2612
|View full text |Cite
|
Sign up to set email alerts
|

Role ofCD14Promoter Polymorphisms inHelicobacter pyloriInfection–Related Gastric Carcinoma

Abstract: Purpose: Genetic variation in CD14 may affect CD14 expression and susceptibility to Helicobacter pylori infection^related cancers. This study examined functional single nucleotide polymorphisms (SNP) in the CD14 promoter and their associations with risk of developing gastric carcinoma in relation to H. pylori infection. Experimental Design: Thirty individual DNAs were sequenced to identify variants, and the function of the variants was examined by reporter gene assays. Genotypes and haplotypes were analyzed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 55 publications
1
41
2
1
Order By: Relevance
“…Because this is an ongoing molecular epidemiologic study of gastric cancer, a report on part of this case-control panel (both n ¼ 470) was published previously. 10 Among these cSNPs, only the Ala2Asp SNP has a minor allelic frequency >1% in the Chinese population (HapMap data release 21a) and, thus, was selected for genotyping in the current study. Genomic DNA was extracted from peripheral blood lymphocytes in all participants.…”
Section: Individuals For Case-control Analysismentioning
confidence: 99%
“…Because this is an ongoing molecular epidemiologic study of gastric cancer, a report on part of this case-control panel (both n ¼ 470) was published previously. 10 Among these cSNPs, only the Ala2Asp SNP has a minor allelic frequency >1% in the Chinese population (HapMap data release 21a) and, thus, was selected for genotyping in the current study. Genomic DNA was extracted from peripheral blood lymphocytes in all participants.…”
Section: Individuals For Case-control Analysismentioning
confidence: 99%
“…Specifically, membrane CD14, together with TLR4, binds to LPS and transmits signals into the nucleus, activating the release of a series of cytokines (8,9), which may promote gastric carcinogenesis. For example, a previous study found that certain polymorphisms of the CD14 gene promoter region are associated with the susceptibility to gastric cancer, which could be due to alterations in CD14 expression (10).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that there is a high expression of CD14 and TLR4 in tissues infected with H. pylori, particularly in gastric cancer tissues (14,15). Another study reported that a functional polymorphism of the CD14 promoter was able to affect the expression of CD14 and increase the risk of gastric cancer (16), suggesting that the CD14 protein is important in the transduction of inflam- (17) used LPS to treat A549 non-small cell lung cancer cells and observed that LPS induced tumor cell viability in a time-and dose-dependent manner. However, this effect was inhibited by CD14 and TLR4-neutralizing antibodies.…”
Section: Discussionmentioning
confidence: 99%